2000
DOI: 10.1063/1.126791
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence and current transport mechanisms in AlxGa1−xN Schottky rectifiers

Abstract: GaN and Al0.25Ga0.75N lateral Schottky rectifiers were fabricated either with (GaN) or without (AlGaN) edge termination. The reverse breakdown voltage VB (3.1 kV for GaN; 4.3 kV for AlGaN) displayed a negative temperature coefficient of −6.0±0.4 V K−1 for both types of rectifiers. The reverse current originated from contact periphery leakage at moderate bias, while the forward turn-on voltage at a current density of 100 A cm−2 was ∼5 V for GaN and ∼7.5 V for AlGaN. The on-state resistances, RON, were 50 mΩ cm2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] The GaN materials system has a high breakdown field, can operate at high temperatures ͑ϳ500°C͒ and has reasonable thermal conductivity if bulk wafers are available. [1][2][3][4][5][6][7][8][9][10][11] The GaN materials system has a high breakdown field, can operate at high temperatures ͑ϳ500°C͒ and has reasonable thermal conductivity if bulk wafers are available.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The GaN materials system has a high breakdown field, can operate at high temperatures ͑ϳ500°C͒ and has reasonable thermal conductivity if bulk wafers are available. [1][2][3][4][5][6][7][8][9][10][11] The GaN materials system has a high breakdown field, can operate at high temperatures ͑ϳ500°C͒ and has reasonable thermal conductivity if bulk wafers are available.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The use of wide band gap materials such as GaN or SiC should alleviate some of the problems with using SiC for these applications, such as the need for extensive thermal management and vertical or parallel connection of devices in order to withstand the very high voltages and on-state currents. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] p-i-n rectifiers are expected to have larger reverse blocking voltages, V B , than Schottky rectifiers, but inferior switching speeds due to stored charge and higher forward turn-on voltages, V F . 13 All of the GaN p-i-n rectifiers reported to date have been heteroepitaxial devices, with the active layers grown on Al 2 O 3 substrates.…”
mentioning
confidence: 99%
“…Recent studies on GaN-based Schottky and pn junction diodes have reported negative temperature coefficients because of defect-assisted tunneling through the surface or defect states, [5][6][7][8] while we have shown almost temperature-independent characteristics of the breakdown voltage for GaN-based vertical conducting pn junction diode. 9) Then, it is of considerable interest to investigate the high-temperature characteristics of Al x Ga 1Àx N-based vertical conducting diodes.…”
Section: Introductionmentioning
confidence: 95%